Behavioral Mathematics for Game AI - Mark, Dave (Course Technology, 2012)
Human behavior is never an exact science, making the design and programming of artificial intelligence that seeks to replicate human behavior difficult. Usually, the answers cannot be found in sterile algorithms that are often the focus of artificial intelligence programming.